Application of Artificial Neural Network (ANN) for frequency response in power system dynamics - Mohd. Jelani, Azliza (2014)
This paper presents a new application of Artificial Neural Network (ANN) for frequency response in system dynamics. In order to perform the ANN, the power flow solution is obtained first for the system to be studied. The purpose of load flow simulation is to get some operating parameters which influence the system frequency behavior. The transient simulation of a power system is then simulated by DigSilent Simulator to analyze the frequency response of the system when it subjected to a disturbance. Simulations were carried out on the IEEE 9-Bus Test System considering load injection on the system. The data collected from transient simulation are then used as inputs to the ANN while the frequency response of the systems as the ANN output. The Lavernberg–Marquardt optimization utilizing very fast propagation algorithm has been adopted for training feed–forward Neural– Network. To verify the effectiveness of the proposed application of ANN method, its performance is compared with the actual value obtained from transient simulation. The ANN provides promising results in terms of error estimation, accuracy and computation time